Stilobezzia Kieffer (Diptera: Ceratopogonidae) from the Brazilian Amazon: three new species, redescription of S. (Stilobezzia) maculata Lane and new records - Silva, Irene M. Da; Ferreira-Keppler, Ruth L.; Cazorla, Carla G. (Zootaxa, 2023)
Three new species of Stilobezzia Kieffer, 1911 are described and illustrated from the Brazilian Amazon, two in the nominotypical subgenus Stilobezzia: S. (Stilobezzia) brasiliensis n. sp. and S. (Stilobezzia) campinaranensis n. sp., and one in the subgenus Acanthohelea: S. (Acanthohelea) medialuna n. sp. We also redescribe and re-illustrate S. (Stilobezzia) maculata Lane based on the examination of type material and additional specimens. In addition, S. (Eukraiohelea) proxima Cazorla & Felippe-Bauer, S. (Eukraiohelea) quasielegantula Cazorla & Felippe-Bauer, S. (Stilobezzia) chaconi Macfie, S. (Stilobezzia) glauca Macfie, and S. (Stilobezzia) maculata are recorded for the first time from the state of Amazonas, northern Brazil. The number of Stilobezzia species in Brazilian Amazon increases from 11 to 19.